Effect of Mass Media on Objectifying of Humans - Keswani, Saumya; Kattu, Kushagra; Wani, Abrar; Balamurugan, J (Journal of Advanced Research in Journalism & Mass Communication, 2018)
Media is a tool that is used to convey mass communication to a larger audience or crowd. It is a good source of entertainment and information and also has a great impact in our day-to-day life. It has its feet everywhere, right from the children to the old people, and it affects each age group differently. As media is the source of information we are dependent upon, it is a support to the people for shaping their opinions and attitudes. In this paper, we have conducted a survey within the indicated age group and determined the influence, the views and opinions of the people. Also, we have identified certain events in media that greatly magnify this issue, and finally suggested a solution to reduce the influence and not objectify humans. How to cite this article: Keswani S, Kattu K, Wani A et al. Effect of Mass Media on Objectifying of Humans. J Adv Res Jour Mass Comm 2018; 5(3): 14-18.